Sustainable elements of the ongoing growth in the demand for halal products in OBOR regional markets - Abbas, Hasnain; Tian, Gang; Faiz, Narmeen; Jiang, Mengyin; Ullah, Hafeez (Frontiers in Nutrition, 2025)
Muslim consumers prioritize the assurance of halal certification when purchasing products for consumption, as adherence to their religious beliefs is paramount. Within the framework of the One Belt One Road (OBOR) initiative, which encompasses approximately 72 countries—nearly half of which are predominantly Muslim—it is essential to recognize the significance of product integrity and authenticity. Given the substantial market potential in these regions, stakeholders must focus on meeting the demand for nutritional halal foods. This approach not only satisfies consumers’ religious requirements but also fosters trust and loyalty within this diverse demographic. An online survey consisting of two segments was conducted, and responses were analyzed using STATA version 16. The survey was disseminated through email, Facebook, and WhatsApp, resulting in a total of 435 responses, of which 399 were deemed complete and suitable for analysis. In the second segment, 279 respondents were evaluated, comprising 18 producers, 33 intermediaries, 70 wholesalers, and 158 retailers, to assess the growing market demand for nutritional halal foods and understand prevailing business trends. The results reveal that a 1-unit increase in the availability of product video links leads to a 63.4% increase in customer demand, while a 1-unit increase in customer belief and satisfaction results in increases of 23.3 and 5% in demand, respectively, highlighting the importance of transparency, religious compliance, and consumer trust in driving demand for halal products. The initial analysis of consumer behavior in OBOR Muslim countries, followed by a thorough examination of producers, intermediaries, wholesalers, and retailers, provides valuable insights into the projected growth in demand for Halal food. With an estimated 1.9 billion Muslims constituting approximately 25.01% of the global population—and 92% residing in OBOR nations—it is evident that halal dietary principles transcend national boundaries. By implementing strategic policies, stakeholders, including policymakers and firm managers, can optimize their efforts to meet the nutritional demands of this expansive market. Furthermore, this study identifies the need for additional exploration into related aspects such as sustainable traceability of quality halal products, brand image clarity, and consumer awareness of supply chain operations.